(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The green marketing mix is now an important strategy for sustainability and to meet the demands of the consumer for green products. it involves green practices that may relate to the development of a product, price, promotion, and channels. with regards to the dairy products, green marketing has gained some importance since consumers prefer to buy these types of products because they are eco-friendly in nature. The green marketing mixes emphasize the message that a brand concerns itself with sustainability through green innovation and other environmental-friendly activities to increase its purchase intentions.